Fiat exchange in finite economies - Dan Kovenock; Casper G. de Vries (Bank of Finland, 1995)
The state of the art of rendering fiat money valuable is either to impose a boundary condition, or to make the boundary condition unimportant by using infinities concerning the sequence of markets and/or the number of agents, so as to circumvent backward induction.We present two models of fiat exchange in deliberately finite economies in which the usage is not imposed.In the first approach agents have incomplete information about their relative position in the trade cycle.The second approach relies on the possibility that multiple non-monetary equilibria of the one-shot game can support monetary equilibria in the repeated game.
URN:NBN:fi:bof-20140807296
Keywords: 330